Understanding, studying, and reading : New Testament essays in honour of John Ashton - Ashton, John, 1931-2016; Rowland, Christopher, 1947-; Fletcher-Louis, Crispin H. T. (Journal for the study of the New Testament. Supplement series ;, 1998)
This collection of essays, largely written by members of the Oxford theological community, was presented to John Ashton on his 65th birthday in 1996. The essays deal with Elijah in Mark, a Q passion narrative, the Gospel thief saying, John's Beloved Disciple, the temple incident (Jn 2.13-25) and history and theology. Outside of the Gospels, they discuss God's wrath in Romans 1, Philippians 1.1-11, Hebrews 4.13, Peter and Paul behind Revelation, and hermeneutical method. Specialists from outside the New Testament field contribute studies of the patristic doctrine of Scripture, the Syriac Diates.